مشكلات الصراع الداخلي وحلّها في القصة القصيرة " البنت والأسد" لمحمد عطية الإبراشي - Faridl Hakim (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
This research examine a child's story or can be called by Cernak by Muhammad Athiyah al Ibrasy. In his book entitled Psychology of Literature, Albert states that psychology symptoms take many forms, for example: shame, love, sadness and so on. So, these form of emotions is the concept of clarifying emotions. Thus, by knowing and identifying these form of emotions the researcher can determine inner conflict. In addition, the researcher also add or display the efforts of the characters in solving the forms of problems experienced by the characters. Through this emotion clarification, the researcher can determine, that in the story there is an inner conflict. Emotion clarification is very helpful for the researcher in analyzing so that the researcher gets the results. This research adopted the descriptive method. Researcher found two components in this story. First, the story has a long process of inner conflict and has stages, so the conflict that experienced by the characters also varies such as a sense of love, sadness, scared and each other. Second, clarification of emotions owned by the characters such as the persistent nature of the collisions that befall themselves and their environment, has an intelligent nature, has a nature of courage, merciful, love and so on.